Трансформация законов распределений при пересчете результатов измерений из логарифмических единиц в абсолютные. - Захаров, И. П.; Шевченко, Н. С.; Сергиенко, М. П.; Штефан, Н. В. (Харківский університет повітряних сил, 2013)
Transformation of laws of distributions at recalculation of results of measurements from logarithmic units in the absolute is considered. Values of kurtosis and sequences of the transformed laws of distributions are resulted. Influence of the law of distribution of entrance value on estimations of measurements uncertainty is investigated.
Keywords: distribution law; transformation; uncertainty in measurement; decibel